The Establishment of Children's Islamic Character Education: Family Communication Study In Padang Leban - M Ridho Syabibi (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: The Establishment of Children's Islamic Character Education: Family Communication Study In Padang LebanThis study aims to look at the phenomenon of Islamic character in children who are still lacking in knowledge about religion, lacking in praying, skipping school, disrespectful, addicted to technology and still lacking in terms of security. This is caused by various factors, especially factors within the family itself, namely parents. However, there are not a few children whose Islamic character is quite good. The formulation of the problem in this research is how to apply family communication in the formation of the Islamic character of children in Padang Leban, Tanjung Kemuning, Kaur. This study aims to determine family communication in the formation of the Islamic character of children in Padang Leban, Tanjung Kemuning, Kaur. The type of research used in this study is (Field research). In this study, the results obtained: the application of family communication in the formation of the Islamic character of children in Padang Leban, Tanjung Kemuning, Kaur, has been carried out well, while the methods used are the habituation method, the exemplary method, and the wisdom method.Abstrak: Pembentukan Pendidikan Karakter Islami Anak: Studi Komunikasi Keluarga Di Padang LebanPenelitian ini bertujuan untuk melihat fenomena karakter islami pada anak yang masih kurang pengetahuan tentang agama, kurang sholat, bolos sekolah, tidak sopan, kecanduan teknologi dan masih kurang dari segi keamanan. Hal ini disebabkan oleh berbagai faktor terutama faktor dalam keluarga itu sendiri yaitu orang tua. Namun, tidak sedikit anak yang karakter islaminya cukup baik. Rumusan masalah dalam penelitian ini adalah bagaimana penerapan komunikasi keluarga dalam pembentukan karakter islami anak di Padang Leban, Tanjung Kemuning, Kaur. Penelitian ini bertujuan untuk mengetahui komunikasi keluarga dalam pembentukan karakter islami anak di Padang Leban, Tanjung Kemuning, Kaur. Jenis penelitian yang digunakan dalam penelitian ini adalah (Field research). Dalam penelitian ini diperoleh hasil: penerapan komunikasi keluarga dalam pembentukan karakter islami anak di Padang Leban, Tanjung Kemuning, Kaur, sudah terlaksana dengan baik, adapun metode yang digunakan adalah metode pembiasaan, metode keteladanan, dan metode kebijaksanaan.